MAKNA IMPLISIT DALAM FILM PURSUIT OF HAPPINESS KARYA GABRIELE MUCCINO - Dede Narawaty (Pujangga: Jurnal Bahasa dan Sastra, 2016)
ABSTRACTThe purpose of this study is to analyze the use of language in the film "Pursuit of Happiness" by Gabriele Muccinoto express the implicit meaning. Besides, the writer hopes that the audience understands the content of the film. Themethod used to analyze the novel is by using qualitative method containing an intrinsic element. After the writeranalyzes the movie "Pursuit of Happiness" through the analysis of implicit meaning, finally the writer can draw theconclusion that there are many implicit meanings in the film "Pursuit of Happiness".Keywords: semantics, meaning change, meaning shift, characters dialogues, narrative texts, languagelearning